Single-step ultrafiltration technique for recovery and purification of Surfactin from fermentation broth - Muhammad Qadri Effendy Mubarak
Several findings and method were improvises as for the downstream processing of surfactin production. An effecient and sensitive High Performance Liquid Chomatography (HPLC) procedure for qualitative and quantitative analysis of surfactin and glucose present in complex fermentation has been successfully improvised without modification of current HPLC equipped with Variable Wavelength Detector (VWD), with the total elution time of 5 minutes and 8 minutes respectively. This rapid analysis makes this technique ideal for fermentation broth optimization and assessment during fermentation process development. The method has been validated and has proven to quantify the glucose and surfactin respectively in standard solution as well as in fermentation broth. The kinetic studies provides important kinetics information for better understanding of interactions of bacterial cell growth and glucose consumption towards surfactin production by B. subtilis MSH1 and B. subtilis ATCC 21322. The maximum concentration of surfactin (Pmax) achieved by B. subtilis MSH1 and B. subtilis ATCC 21332 was 226.17 mg/L and 447.26 mg/L, respectively. The kinetic study of bacterial cell growth of both strains indicated that B. subtilis MSH1 had a specific growth rate (Umax) of 0.224 h-1 and attained a maximum biomass concentration (Xmax) as high as 2.90 g/L after 28 h of fermentation, while B. subtilis ATCC 21332, with Umax of 0.087h-1, attained an Xmax of 2.62 g/L after 45 h of incubation. Under identical fermentation conditions, B. subtilis MSH1 showed higher growth kinetics compared with B. subtilis ATCC 21332 and exhibited higher values of Umax and Xmax. Later, the surfactin present in fermentation broth were extracted by using benchtop cross-flow ultrafiltration unit equipped with hydrosart membrane(HT) and polyethersulfone membrane (PES) with a 10 kDa and 30 kDa molecular weight cut-off (MWCO) using transmembrane pressures (TMP) varying from 0.5-2.0 bar. Permeate flux, rejection coefficient (R) of surfactin and total protein contents in permeates and retentates were measured during the UF to evaluate the characteristic of all membranes towards the recovery and purity of the surfactin final fraction. Surfactin was retained almost completely with a rejection coefficient (R) close to 1.00 for all membranes, with permissible purity ranging from 82% to 88%. The TMPs applied had no significant effect (P<0.05) on R because the membranes pore size were smaller than surfactin micelles. HT10 was achieved better recovery and purity of the final product compared to other membrane used. Later, product characterization analysis was conducted to evaluate the functionality of surfactin final fraction by using surface tension and Fourier Transform Infra-red (FTIR). Result showed close proximity of surface activity in relation to surfactin standard which indirectly indicated the presence of impurities in the final fraction did not affect the original surfactin functionality. FTIR spectra confirmed that the UF retentate contains aliphatic hydrocarbons as well as a peptide-like moiety, which correspond to the structure of surfactin.